Respuesta :

Answer:

See below ~

Step-by-step explanation:

Let the bases be x and x + 6.

Substituting the known values into the formula :

  • A = 1/2 x (a + b) x h
  • 48 = 1/2 x (x + x + 6) x 4
  • 2x + 6 = 24
  • 2x = 18
  • x = 9

The base lengths are :

  1. x = 9 inches
  2. x + 6 = 9 + 6 = 15 inches

Answer:

One base is [tex]\large \boxed{\sf 9}[/tex]  inches for one of the bases and [tex]\large \boxed{\sf 15}[/tex] inches for the other base.

[tex]\large \boxed{\sf 24}=\sf(b_1+b_2)[/tex].  Use guess and check to find two numbers that add to [tex]\large \boxed{\sf 24}[/tex] with one number 6 more than the other to get

[tex]\large \boxed{\sf 9}[/tex]  inches for one of the bases and [tex]\large \boxed{\sf 15}[/tex] inches for the other base.

Step-by-step explanation:

[tex]\textsf{Area of a trapezoid}= \sf \dfrac{1}{2}(b_1+b_2)h \quad \textsf{(where b are the bases and h is the height)}[/tex]

Given:

  • Area = 48 in²
  • h = 4 in

Substitute given values into the formula to find (b₁ + b₂) :

[tex]\implies \sf 48=\dfrac{1}{2}(b_1+b_2)4[/tex]

[tex]\implies \sf \dfrac{48}{4}=\dfrac{1}{2}(b_1+b_2)[/tex]

[tex]\implies \sf 12=\dfrac{1}{2}(b_1+b_2)[/tex]

[tex]\implies \sf 12 \cdot 2=(b_1+b_2)[/tex]

[tex]\implies \sf 24=(b_1+b_2)[/tex]

Therefore:

[tex]\large \boxed{\sf 24}=\sf(b_1+b_2)[/tex]

Let:

  • Base b₁ = x in
  • Base b₂ = (x + 6) in

[tex]\implies \sf (b_1+b_2)=24[/tex]

[tex]\implies \sf x+x+6=24[/tex]

[tex]\implies \sf 2x+6=24[/tex]

[tex]\implies \sf 2x=18[/tex]

[tex]\implies \sf x=9[/tex]

[tex]\sf If\:b_1=9\:in,\:then\:b_2=9+6=15\:in[/tex]

Therefore,

  • Base b₁ = 9 in
  • Base b₂ = 15 in